Dynamic covalent diarylbibenzofuranone-modified nanocellulose: mechanochromic behaviour and application in self-healing polymer composites. Issue 13 (21st March 2017) - Imato, K.; Natterodt, J. C.; Sapkota, J.; Goseki, R.; Weder, C.; Takahara, A.; Otsuka, H.
Abstract : Surface mechanochemistry of nanocelluloses modified with a dynamic covalent mechanophore is investigated, and self-healing composites with the celluloses are developed. Abstract : The surface of cellulose nanocrystals (CNCs) was modified with a scissile but reversibly recombinable dynamic covalent mechanophore, and the activation of the mechanophore on the CNC surface in bulk was investigated. The recombination behaviour of the activated surface-modified mechanophore exhibited high sensitivity to mechanical stress because of the limited molecular mobility. The modified CNCs could be used to effectively reinforce a self-healable polymer containing similar dynamic covalent linkages through the formation of reversible covalent bonds between the CNC surfaces and the polymer matrix, while the nanocomposite retained the ability to heal. The results of the present study appear to be broadly useful for designing composite materials with fascinating functional properties such as damage self-reporting and self-healing.